CT Hounsfield units in assessing bone and soft tissue quality in the proximal femur: A systematic review focusing on osteonecrosis and total hip arthroplasty. - Tong-Jie Yang; Peng-Peng Wen; Xin Ye; Xiao-Feng Wu; Cheng Zhang; Shi-Yi Sun; Zi-Xuan Wu; Guang-Yi Zhang; Yi-Fei Sun; Ren Ye; Cheng-Kun Zhou; Hai-Jun He (PLoS ONE)
Background Computed tomography (CT) Hounsfield Units (HU) offer valuable insights into the changes in bone and soft tissue densities, playing a crucial role in the diagnosis and management of various proximal femur conditions. This systematic review aims to consolidate the application of HU in assessing tissue quality in the proximal femur, with a special focus on osteonecrosis of the femoral head (ONFH) and implications for total hip arthroplasty (THA), thereby addressing unresolved issues in these areas. Methods We conducted a comprehensive literature search on MEDLINE/PubMed, EMBASE, Google Scholar, SpringerLink, Scops, Web of Science, and Bentham Science Publishers from inception to January 2024, following the PRISMA guidelines, to retrieve all studies relevant to the application of HU in assessing both bone and soft tissue quality of the proximal femur, particularly in the context of ONFH and THA. We systematically evaluated the key findings extracted from the included articles. Results This systematic review included a total of 58 studies, involving 15,668 patients. The sample sizes ranged from 50 to 685, with the CT slice thickness varying from 0.5 mm to 10 mm. The results mainly focused on three areas: (1) the relationship between HU and the density of proximal femoral tissues (n = 33); (2) the assessment of HU in predicting the risk of femoral head collapse (n = 10); (3) the application of HU during the perioperative period of THA (n = 15). Conclusion (1) HU can effectively contribute to the evaluation of bone and soft tissue densities in the proximal femur, and reflect local stress changes. (2) In ONFH patients, bone density does not decrease in the necrotic area of the femoral head before collapse. However, abnormally elevated HU at the outer boundary of the necrotic lesion are significant in assessing collapse risk. (3) HU can be used to preoperatively assess hip bone quality for THA, guide surgical approaches, predict intraoperative fractures, monitor postoperative bone ingrowth or absorption, identify and quantitatively evaluate periprosthetic loosening, and guide postoperative rehabilitation.